2017
DOI: 10.1002/jmor.20772
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and microscopic analyses in flexor tendons of the tarsometatarso‐phalangeal joint of ostrich (Struthio camelus) foot with energy storage and shock absorption

Abstract: Flexor tendons function as energy storage and shock absorption structures in the tarsometatarso-phalangeal joint (TMTPJ) of ostrich feet during high-speed and heavy-load locomotion. In this study, mechanisms underlying the energy storage and shock absorption of three flexor tendons of the third toe were studied using histology and scanning electron microscopy (SEM). Macroscopic and microscopic structures of the flexor tendons in different positions of TMTPJ were analyzed. Histological slices showed collagen fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…In a similar way, the possible distinctive loading and stress patterns of the patellar tendon in molossids might be favoring the presence of one or more suprapatellae in these taxa. Differences in the properties of tendons playing different functional roles-e.g., those that power locomotion versus those that act to limiting excessive flexion of joints-have been reported in other vertebrates (e.g., Zhang et al, 2017), and the same may apply to sesamoids. Thus, the rela-tively large number of sesamoids in molossids and Desmodus might result from the additional functional demands resulting from regularly employing two very different types of locomotion (i.e., flapping flight vs. quadrupedal cursorial locomotion), a hypothesis first proposed by Reyes-Amaya et al (2017).…”
Section: Sesamoids and Quadrupedal Locomotionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a similar way, the possible distinctive loading and stress patterns of the patellar tendon in molossids might be favoring the presence of one or more suprapatellae in these taxa. Differences in the properties of tendons playing different functional roles-e.g., those that power locomotion versus those that act to limiting excessive flexion of joints-have been reported in other vertebrates (e.g., Zhang et al, 2017), and the same may apply to sesamoids. Thus, the rela-tively large number of sesamoids in molossids and Desmodus might result from the additional functional demands resulting from regularly employing two very different types of locomotion (i.e., flapping flight vs. quadrupedal cursorial locomotion), a hypothesis first proposed by Reyes-Amaya et al (2017).…”
Section: Sesamoids and Quadrupedal Locomotionmentioning
confidence: 70%
“…The functions of sesamoids have been a matter of speculation for decades. Sesamoids have generally been thought to function in association with the mechanical stress exerted on tendons as they wrap around a bony edge or a joint, possibly improving the ability of these tendons to respond to compressive load, pressure, tensile strain, and vibration (Carlsöö, 1982;Davin, 1921a, 1921b;Nussbaum, 1982;Sarin et al, 1999;Jerez et al 2010;Ponssa et al, 2010;Tsai and Holliday, 2011;Otero and Hoyos, 2013;Regnault et al, 2016;Abdala et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bizarro, ; Mottershead, ) and have intrigued researchers for centuries. Diverse functions have been attributed to sesamoids, such as tendon protection against friction (Le Minor, ) or compression, tension and rotation (Carlsöö, ; Nussbaum, ; Sarin et al, ; Otero & Hoyos, ; Regnault et al, , b ; Abdala, Vera & Ponssa, ; Zhang et al, ), increasing tendon leverage, or redirecting the pull of tendons (Alexander & Dimery, ; Vickaryous & Olson, ; Evans & De Lahunta, ; Regnault, Pitsillides & Hutchinson, ). The literature shows that all of these functions are accomplished by sesamoids.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that there were multiple tendons attached to the tarsometatarsus of the ostrich by dissection. Hutchinson et al demonstrated that the flexor digitorum longus tendon serves as a "spring" during the stance phase, and the extensor digitorum longus tendon serves as a support during the lift-off phase [30,31]. The interphalangeal ligament of the ostrich foot controls the opening and closing of the two toes.…”
Section: Design and Fabrication Of The Bionic Mechanical Footmentioning
confidence: 99%